Simulation study of large production network robustness in uncertain environment. Issue 1 (2015) - Putnik, Goran D.; Škulj, Gašper; Vrabič, Rok; Varela, Leonilde; Butala, Peter
Abstract: Robustness is an important success factor for production networks in which the operation of enterprises is subjected to an uncertain environment. In this paper, the robustness of networks is studied as a function of network size. The study is performed through a simulation experiment in which the uncertain environment is modelled by introducing perturbations in demand. The decision-making model mimics the behaviour of socially connected human subjects. The results show how robustness and production rate are affected by system size and social network structure, and how this is relevant for the design and operation of future manufacturing systems.